Modelling motorcycle ownership in Malaysia:case study of Pulau Pinang. - Leong, Lee Vien; Mohd. Sadullah, Ahmad Farhan; Wan lbrahim, Wan Hashim; Mohd Shafie, Shafida Azwina (Universiti Sains Malaysia, 2006)

(untitled)
In Malaysia, vehicles composition registered annually consists mainly of passenger cars, motorcycles, buses, medium and heavy lorries and almost 50% of the vehicles registered are motorcycles.